In situ ultra-small-angle X-ray scattering study under uniaxial stretching of colloidal crystals prepared by silica nanoparticles bearing hydrogen-bonding polymer grafts - Ryohei Ishige; Gregory A. Williams; Yuji Higaki; Noboru Ohta; Masugu Sato; Atsushi Takahara; Zhibin Guan (IUCrJ, 2016)
A molded film of single-component polymer-grafted nanoparticles (SPNP), consisting of a spherical silica core and densely grafted polymer chains bearing hydrogen-bonding side groups capable of physical crosslinking, was investigated by in situ ultra-small-angle X-ray scattering (USAXS) measurement during a uniaxial stretching process. Static USAXS revealed that the molded SPNP formed a highly oriented twinned face-centered cubic (f.c.c.) lattice structure with the [11−1] plane aligned nearly parallel to the film surface in the initial state. Structural analysis of in situ USAXS using a model of uniaxial deformation induced by rearrangement of the nanoparticles revealed that the f.c.c. lattice was distorted in the stretching direction in proportion to the macroscopic strain until the strain reached 35%, and subsequently changed into other f.c.c. lattices with different orientations. The lattice distortion and structural transition behavior corresponded well to the elastic and plastic deformation regimes, respectively, observed in the stress–strain curve. The attractive interaction of the hydrogen bond is considered to form only at the top surface of the shell and then plays an effective role in cross-linking between nanoparticles. The rearrangement mechanism of the nanoparticles is well accounted for by a strong repulsive interaction between the densely grafted polymer shells of neighboring particles.